New nitrogen-containing metabolites from cultures of rice false smut pathogen Villosiclava virens. Issue 2 (17th January 2021) - Wang, Ali; Li, Peng; Han, Peipei; Gu, Gan; Shan, Tijiang; Lai, Daowan; Zhou, Ligang
Abstract: Two new nitrogen-containing metabolites methyl N -acetyl- O -(4-acetylphenyl)- L -homoserinate (1 ), dimethyl (1 H -indole-3-carbonyl)- D -glutamate (2 ), and two new natural products, 1, 2- O -isopropylidene- D -mannitol (3 ), N -acetyl- β -methyl- L -phenylalanine (4 ), along with five known compounds (5 –9 ) were isolated from the rice false smut pathogen Villosiclava virens UV-8b cultured in the solid rice medium. The structures were elucidated by spectroscopic analysis and by comparison of their physical and spectroscopic data with the literature. These metabolites were evaluated for their antibacterial and phytotoxic activities. Compounds 5 –7 showed weak inhibition against the tested bacteria, while compounds 4 –6 and 9 displayed inhibitory activity against the radicle elongation of rice seeds. GRAPHICAL ABSTRACT: